ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DALAM PEMBAYARAN REKENING LISTRIK DI KOTA PLAJU PALEMBANG - Ilhamsyah .; Agus Mulyani (Universitas PGRI Palembang, 2013)
Customer satisfaction is a happy or disappointed feeling of people thatappear after comparing the result of product thought with the result hoped. Customer satisfaction is influenced by perception of some quality, either service or product. One of factors that determine customer satisfaction is customer perception about service quality focused at five dimensions of service quality; they are physical evident, reliability, perceptive effort, guarantee, and empathy.One of organizations that work in service to public is PT. PLN (Persero) Plaju Palembang. Meanwhile, one of many kinds of service given to public is Payment Point Online Bank (PPOB). Payment Point Online Bank (PPOB) is a payment point of electrical claim payment from PLN customer by online with bank. The aim of this research is to analyze physical evident, reliability, perceptive effort, guarantee, and empathy influence to PLN customer satisfaction with PPOB system. Population in this research is PLN Plaju Ilir customer and couse second research is PLN Plaju Ulu that paid an electrical claim by Payment Point Online Bank (PPOB) system in May 2013 – Oktober 2013amount 10.378 customers. Sample in this research is 100 respondents. Technique of sample taking in this research is done by accidental sampling. Kind of data is primer. The method of data collection uses questionnaire. Analysis technique used is multiple regressions. The result of analysis by using SPSS Version 13 shows that: Quality of care has positive influence on customer satisfaction, from the result obtained showed regression assurance (b4 =0.285) became the biggest factor affecting customer satisfaction, then tangibles (b1 =0.209),responsiveness (b3=0.202),reability (b2= 0.163), empaty (b5= 0.160) became the lowest factor affecting customer satisfaction of Wilayah Plaju Ulu couse of the Wilayah Plaju Ilir. The quality of care has positive influence on customer satisfaction, from the result obtained showed regression assurance (b4 =0.265) became the biggest factor affecting customer satisfaction, then tangibles (b1 =0.205), responsiveness (b3=0.207), reability (b2= 0.157), empaty (b5= 0.160) became the lowest factor affecting customer satisfaction.Testing the hypothesis of partially independent variables significant, because the significant of all values <0.05 hypothesis test simultaneously of independent variable is significant because significant value is < 0, 05. Determination coefficient shows that variable capability of physical evident, reliability, perceptive effort, guarantee, and empathy in explaining customer satisfaction of Electrical Claim Payment Customer Service Wilayah Plaju Ulu is amount 91,6%. Couse Wilayah Plaju Ilir is amount 90,8%. The Testing the hypothesis of second test significant system Payment Point Online Bank (PPOB) of Plaju Ulu and Plaju Ilir is right to system PPOB Kata kunci: Kualitas Pelayanan dan Kepuasan Pelanggan